Relationships between inflammatory cytokine and cortisol responses in firefighters exposed to simulated wildfire suppression work and sleep restriction. Issue 11 (24th November 2015) - Wolkow, Alexander; Aisbett, Brad; Reynolds, John; Ferguson, Sally A.; Main, Luana C.
Abstract: The interplay between inflammatory and cortisol responses modulates an appropriate response to a stressor. Exposure to severe stressors, however, may alter the actions and relationships of these responses and contribute to negative health outcomes. Physical work and sleep restriction are two stressors faced by wildland firefighters, yet their influence on the relationship between inflammatory and cortisol responses is unknown. The aim of the present study was to quantify the relationship between the cytokine and cortisol responses to sleep restriction while performing simulated physical wildfire suppression work. Firefighters completed 3 days of simulated physical firefighting work separated by either an 8‐h (Control condition; n = 18) or 4‐h sleep (Sleep restriction condition; n = 17) opportunity on each of the two nights. Salivary cortisol and inflammatory cytokines (IL‐6, IL‐8, IL‐1 β, TNF‐ α, IL‐4, and IL‐10) were measured throughout each day. An increase in morning IL‐6 was related to a rise (6.2%, P = 0.043) in evening cortisol among firefighters in the sleep restriction condition. Higher morning IL‐6 levels were related to increased (5.3%, P = 0.048) daily cortisol levels, but this relationship was not different between conditions. Less pronounced relationships were demonstrated between TNF‐ α, IL‐10, IL‐4, and cortisol independent of the sleep opportunity, but relationships did not persist after adjusting for demographic factors and other cytokines. These findings quantify the relationship between cytokine and cortisol responses among wildland firefighters exposed to simulated occupational stressors. Potential disturbances to the IL‐6 and cortisol relationship among sleep‐restricted firefighters' supports further investigations into the negative health effects related to possible imbalances between these systems. Abstract : The interplay between cytokine and cortisol responses modulates an appropriate response to a stressor. Exposure to severe stressors, however, may alter the relationships between these responses and contribute to negative health outcomes. This study advances our understanding of this area by investigating the physiological relationship between cytokine and cortisol levels to the stressors of physical work and sleep restriction involved in firefighting. Potential disturbances to the IL‐6 and cortisol relationship among sleep‐restricted firefighters' supports further investigations into the health effects related to imbalances between these responses.